Single‐Component‐Based White Light Photoluminescence Emission via Selective Photooxidation in an Organic–Polymer Hybrid System. (4th December 2017) - Lee, Minkyung; Song, Intek; Hong, Misun; Koo, Jin Young; Choi, Hee Cheul
Abstract: White light‐emitting phenothiazine‐poly(dimethylsiloxane) (PTZ–PDMS ) composites are formed by a photooxidation reaction. The oxidizedPTZ species, i.e., PTZ cation radicals and dication species, are created by electron transfer from thePTZ molecules toPDMS under UV irradiation. In situ UV–vis and electron spin resonance (ESR) spectroscopies are carried out after UV exposure ofPTZ–PDMS, and the results provide evidence for the spontaneous ionization ofPTZ . The spectral changes indicate the formation ofPTZ + (radical cation) andPTZ 2+ (dication) within the PDMS matrix. Moreover, a combination ofPTZ, PTZ +, andPTZ 2+, together with the PDMS matrix, show an unexpected emission of white light with Commission Internationale de L'Eclairage coordinates of 0.34 and 0.32, which are close to those of pure white light. These findings potentially offer a new route and strategy for the development of flexible white light‐emitting materials. Abstract : Single‐component white light emitters! White light‐emitting phenothiazine–poly(dimethylsiloxane) (PTZ–PDMS ) composites are prepared by photooxidation in air. Only thePTZ–PDMS composites prepared by photooxidation in air emit white photoluminescent light under UV irradiation, and the oxidizedPTZ show high stability within the PDMS matrix.